Sexually dimorphic transcriptional programs of early-phase response in regenerating peripheral nerves - Chernov, Andrei V.; Shubayev, Veronica I. (Frontiers in Molecular Neuroscience, 2022)
The convergence of transcriptional and epigenetic changes in the peripheral nervous system (PNS) reshapes the spatiotemporal gene expression landscape in response to nerve transection. The control of these molecular programs exhibits sexually dimorphic characteristics that remain not sufficiently characterized. In the present study, we recorded genome-wide and sex-dependent early-phase transcriptional changes in regenerating (proximal) sciatic nerve 24 h after axotomy. Male nerves exhibited more extensive transcriptional changes with male-dominant upregulation of cytoskeletal binding and structural protein genes. Regulation of mRNAs encoding ion and ionotropic neurotransmitter channels displayed prominent sexual dimorphism consistent with sex-specific mRNA axonal transport in an early-phase regenerative response. Protein kinases and axonal transport genes showed sexually dimorphic regulation. Genes encoding components of synaptic vesicles were at high baseline expression in females and showed post-injury induction selectively in males. Predictive bioinformatic analyses established patterns of sexually dimorphic regulation of neurotrophic and immune genes, including activation of glial cell line-derived neurotrophic factor Gfra1 receptor and immune checkpoint cyclin D1 (Ccnd1) potentially linked to X-chromosome encoded tissue inhibitor of matrix proteinases 1 (Timp1). Regulatory networks involving Olig1, Pou3f3/Oct6, Myrf, and Myt1l transcription factors were linked to sex-dependent reprogramming in regenerating nerves. Differential expression patterns of non-coding RNAs motivate a model of sexually dimorphic nerve regenerative responses to injury determined by epigenetic factors. Combined with our findings in the corresponding dorsal root ganglia (DRG), unique early-phase sex-specific molecular triggers could enrich the mechanistic understanding of peripheral neuropathies.